THE REPUBLIC OF UZBEKISTAN IN THE WORLD MAP. MINERAL AND RAW RESOURCES OF UZBEKISTAN ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides a comprehensive overview of Uzbekistan's mineral and raw material resources, highlighting their significance in shaping the country's economy and global standing. The piece explores Uzbekistan's geographical context, historical background, and post-independence developments, emphasizing the country's pivotal location in Central Asia and its role in the ancient Silk Road trade routes. The article delves into Uzbekistan's diverse mineral wealth, including gold, copper, uranium, natural gas, and oil, with specific mentions of key mining operations such as the Muruntau Gold Mine and the Navoi Mining and Metallurgical Combine. It also discusses the government's initiatives to attract foreign investment, modernize the mining sector, and promote sustainable resource management. Moreover, the annotation underscores the strategic importance of Uzbekistan's resources in fostering international partnerships and economic growth. It highlights the country's commitment to transparency, responsible resource utilization, and long-term development goals. Overall, this annotation provides a succinct summary of the article's key points, offering insights into Uzbekistan's mineral sector and its implications for global economic dynamics and regional cooperation.